Predicting Currency Fluctuations and Crises : Do Resident Firms Have an Informational Advantage? - Schmukler, Sergio L. 1997- (The World Bank, 1999)
December 1999 - Markets have had limited success predicting crises and might do better by drawing on private information available to resident enterprise managers, who seem to know better than markets about future movements in exchange rates. Kaufmann, Mehrez, and Schmukler investigate whether resident enterprise managers have an informational advantage about the countries in which they work. They propose a method for extracting information available to resident managers but unknown to investors and forecasters. They test their hypothesis of informational advantage using a unique data set, the Global Competitiveness Survey. The survey asks local managers about their outlook for the country in which they reside. They find that local managers do have useful private information. Local managers' responses improve on conventional forecasts of future volatility and changes in the exchange rate, which are based on economic fundamentals or interest rate differentials. They find that the local business community perceived in advance the recent crises in the Republic of Korea, Russia, and Thailand, but not those in Indonesia and Malaysia. Markets have had limited success predicting crises and might do better by drawing on private information available to resident enterprise managers, who seem to know better than markets about future movements in exchange rates. This paper - a product of Governance, Regulation, and Finance, World Bank Institute - is part of a larger effort in the institute to understand the roles of transparency and governance. The authors may be contacted at dkaufmann@worldbank.org, mehrezg@gunet.georgetown.edu, or sschmukler@worldbank.org